The ode less travelled : unlocking the poet within - Fry, Stephen, ....- (London : Arrow, 2007)
Stephen Fry believes that if you can speak and read English you can write poetry. But it is no fun if you don't know where to start or have been led to believe that Anything Goes. Stephen, who has long written poems, and indeed has written long poems, for his own private pleasure, invites you to discover the incomparable delights of metre, rhyme and verse forms. Whether you want to write a Petrarchan sonnet for your lover's birthday, an epithalamion for your sister's wedding or a villanelle excoriating the government's housing policy, The Ode Less Travelled will give you the tools and the confidence to do so. Brimful of enjoyable exercises, witty insights and simple step-by-step advice, The Ode Less Travelled guides the reader towards mastery and confidence in the Mother of the Arts.
Poëzie ; literaire techniek